Preventive paradox?: postoperative outcomes after risk-reducing mastectomy and direct-to-implant breast reconstruction : original article - Knoedler, Samuel; Jiang, Jun; Moog, Philipp; Alfertshofer, Michael; Machens, Hans-Guenther; Kehrer, Andreas; Hundeshagen, Gabriel; Knoedler, Leonard; Könneker, Sören; Kim, Bong-Sung; Orgill, Dennis P.; Panayi, Adriana C. (Clinical breast cancer, 2024)
Background - Risk-reducing mastectomy (RRM) with direct-to-implant (DTI) breast reconstruction is becoming increasingly important in breast cancer prevention. While the oncological benefits of RRM-DTI are well documented, there is a paucity of studies investigating its perioperative safety. - Methods - The ACS-NSQIP database (2008-2022) was queried to identify all patients who underwent RRM-DTI. Outcomes of interest included 30-day occurrence of reoperation, readmission, and surgical and medical complications. Multivariate logistic regression was used to determine factors associated with postoperative complications. - Results - A total of 1019 patients were included, with a mean age and BMI of 42.8 ± 10.9 years and 25.7 ± 5.8 kg/m², respectively. Complications occurred in 142 (14.0%) cases, with 103 (10.1%) reoperations and 51 (5.0%) readmissions. 62 (6.3%) surgical complications were recorded, the majority of which were superficial incisional infection (n = 19; 1.9%) and organ space infections (n = 19; 1.9%). Medical complications were rare (n = 13; 1.3%). Multivariable analyses revealed that higher BMI was significantly associated with any (OR:1.06, P < .0001), surgical (OR:1.08, P < .0001), and medical complications (OR:1.08, P = .04). Patients with bleeding disorders were at a significantly higher risk of any complications (OR:5.5, P = .03), while outpatient setting (OR:1.9, P = .03) and corticosteroid use (OR:6.6, P = .01) were identified as independent predictors of surgical complications. - Conclusion - The risk of adverse events following RRM-DTI should not be underestimated, with a 30-day complication rate of 14%. Higher BMI, bleeding disorders, outpatient setting, and corticosteroid use were identified as risk factors. These findings underscore the need for thorough preoperative risk stratification, patient counseling, and health optimization to optimize surgical outcomes.
Gesehen am 10.07.2025